Effects of Front-End Planning under Fast-Tracked Project Delivery Systems for Industrial Projects. Issue 3 (3rd July 2018) - Sindhu, Jayakrishnan; Choi, Kunhee; Lavy, Sarel; Rybkowski, Zofia K.; Bigelow, Ben F.; Li, Wei
ABSTRACT: Front-end planning (FEP) may be a key element in project success because it helps project participants more efficiently mitigate risk and define project objectives in the preplanning phase. However, very little is known about the effect of FEP for industrial project performance under different project delivery systems. To this end, this study investigated the impact of FEP on project performance by focusing on two widely used fast-track delivery methods: design-build (DB) and construction manager at risk (CMR), compared to the benchmarking conventional design-bid-build (DBB). The Spearman's correlation analysis and Kruskal-Wallis test were performed on a real-world dataset, obtained from the Construction Industry Institute (CII), which comprised 438 industrial projects built between 1990 and 2010 in the US. The correlation analysis results revealed that better FEP resource allocation could help more design packages be completed efficiently and accurately to accelerate the fast-track process. The pair-wise comparison analysis results confirmed that there is no significant evidence to examine particular difference of schedule performance between CMR and DB. On the other hand, the results highlighted that project cost performance under DB were better than CMR. The results and findings of this study will help decision-makers choose appropriate project delivery methods for given project priorities.